2020
DOI: 10.1128/mbio.00443-20
|View full text |Cite
|
Sign up to set email alerts
|

Minimalistic Cellulosome of the Butanologenic Bacterium Clostridium saccharoperbutylacetonicum

Abstract: Clostridium saccharoperbutylacetonicum is a mesophilic, anaerobic, butanol-producing bacterium, originally isolated from soil. It was recently reported that C. saccharoperbutylacetonicum possesses multiple cellulosomal elements and would potentially form the smallest cellulosome known in nature. Its genome contains only eight dockerin-bearing enzymes, and its unique scaffoldin bears two cohesins (Cohs), three X2 modules, and two carbohydrate-binding modules (CBMs). In this study, all of the cellulosome-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…[ 25 ] X2 modules have been described to bind to different polysaccharides, such as cellulose and chitin, [ 18,19 ] and those found in bacterial cell walls, [ 25 ] but also to possibly stabilize the structure of the neighboring Coh domains. [ 26 ] More in detail, the binding affinity of CbpA X2 domains for C. cellulovorans cell wall fragments is lower than that for cellulose or chitin. [ 24 ] Surface‐display of C. cellulovorans cellulosomes is probably mediated by multiple proteins.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] X2 modules have been described to bind to different polysaccharides, such as cellulose and chitin, [ 18,19 ] and those found in bacterial cell walls, [ 25 ] but also to possibly stabilize the structure of the neighboring Coh domains. [ 26 ] More in detail, the binding affinity of CbpA X2 domains for C. cellulovorans cell wall fragments is lower than that for cellulose or chitin. [ 24 ] Surface‐display of C. cellulovorans cellulosomes is probably mediated by multiple proteins.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that in the genome of C. lentocellum , a functional comparatively miniature cellulosome complex is encoded. Interestingly, recently, a small cellulosome was also discovered in Ruminoclostridium saccharoperbutylacetonicum 26 . The genome of this organism encodes two cohesin domains and eight dockerin-bearing enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, putative cellulosomal genes were identified in three mesophilic Clostridium species, including Clostridium acetobutylicum and Clostridium saccharoperbutylacetonicum (Dassa et al 2017). However, only the cellulosome of C. saccharoperbutylacetonicum N1-4 (HMT) appears to be actively expressed, although the organism was still not able to utilize purified cellulose as substrate (Levi Hevroni et al 2020). Levi Hevroni et al hypothesize that cellulosome expression in C. saccharoperbutylacetonicum might be dependent on specific inducers which can only be found in complex substrates, such as plant biomasses (Montoya et al 2001;Levi Hevroni et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, only the cellulosome of C. saccharoperbutylacetonicum N1-4 (HMT) appears to be actively expressed, although the organism was still not able to utilize purified cellulose as substrate (Levi Hevroni et al 2020). Levi Hevroni et al hypothesize that cellulosome expression in C. saccharoperbutylacetonicum might be dependent on specific inducers which can only be found in complex substrates, such as plant biomasses (Montoya et al 2001;Levi Hevroni et al 2020). While we did not examine the cellulose utilization of our strains in this study, we would like to speculate that at least some of them might be able to use a small part of the cellulose content of our complex substrates as a carbon source.…”
Section: Discussionmentioning
confidence: 99%